PENERAPAN PENDEKATAN INKUIRI TERBIMBING DENGAN METODE PICTORIAL RIDDLE UNTUK MENINGKATKAN PEMAHAMAN KONSEP FISIKA SISWA - Chusni, Muhammad Minan (UNIVERSITAS MUHAMMADIYAH METRO, 2016)
The purpose of this study was to determine students improved understanding of physics concepts through the application of guided inquiry approach with metide pictorial riddle on the subject of a simple plane. Type of research is classroom action research with research subjects 29 students of SMP Muhammadiyah Muntilan.Techniques used in collecting data is by direct observation in the classroom and the testing techniques. The analysis of data using qualitative and quantitative analysis.The results showed that the application of guided inquiry learning with pictorial riddle method can improve students understanding of the concept in the first cycle with an average value of 42.93 into 50.71 and the second cycle increased to 67.50 and in the third cycle into 80.71. Similarly, the students motivation to learn physics class is also quite good with a yield of 63.57%.